2013
DOI: 10.1503/cjs.014611
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal epidural steroid injections prevent the need for surgery in patients with sciatica secondary to lumbar disc herniation: a retrospective case series

Abstract: Background:The median orthopedic surgery wait time in Canada is 33.7 weeks, thus alternative treatments for pathologies such as lumbar disc herniations (LDH) are needed. We sought to determine whether transforaminal epidural steroid injections (TFESIs) alleviate or merely delay the need for surgery. Methods:We retrospectively reviewed the charts of patients with LDH who received TFESIs between September 2006 and July 2008. Patient demographics, level and side of pathology, workers' compensation status, levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
0
28
0
4
Order By: Relevance
“…While it has been found that the chance of success of TAESI is higher in the case of pain lasting for shorter periods, the effectiveness of the procedure in patients who have been experiencing chronic pain for longer periods is controversial. [26] In earlier publications, cases not cured within 3-6 months were accepted as chronic low back pain whereas the more recent literature has brought this period down to 7-8 weeks. In the present study, 60% of the patients had been experiencing pain for more than one year prior to the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…While it has been found that the chance of success of TAESI is higher in the case of pain lasting for shorter periods, the effectiveness of the procedure in patients who have been experiencing chronic pain for longer periods is controversial. [26] In earlier publications, cases not cured within 3-6 months were accepted as chronic low back pain whereas the more recent literature has brought this period down to 7-8 weeks. In the present study, 60% of the patients had been experiencing pain for more than one year prior to the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is still substantive criticism, the latest reviews usually point in the same direction: there is proof of moderate to high quality that epidural corticosteroids have a significant but clinically limited effect on lumbosacral radicular pain in comparison with a placebo on leg pain and function during the first weeks, but this effect disappears after 3 months . There are indications that surgery can be avoided in 1 study that assessed this as the primary outcome parameter and various studies that included this as a secondary outcome parameter, although the latter is inconsistent …”
Section: What Is the Place Of Dexamethasone?mentioning
confidence: 99%
“…Along with the controlled studies, several uncontrolled studies performed by spine surgeons evaluating surgery as a primary outcome measure have also found a surgery-sparing effect for ESI. 164,165 In contrast, the large majority of randomized controlled studies evaluating surgery rates as a secondary outcome measure failed to find a difference in operative rates between ESI and placebo treatment, 99, 137,145,146,166Y178 compared with the few that did. 179,180 The difficulty in evaluating surgery rates as a secondary outcome is that nearly all studies are underpowered to detect a difference and incorporate some degree of bias through patient selection.…”
Section: Prevention Of Surgerymentioning
confidence: 99%